Antibiotics used most commonly to treat animals in Europe. (4th October 2014) - De Briyne, N.; Atkinson, J.; Borriello, S. P.; Pokludová, L.
Abstract : The Heads of Medicines Agencies and the Federation of Veterinarians of Europe undertook a survey to gain an insight into European prescribing of antibiotics for animals, in particular to highlight the diseases for which antibiotics are most commonly said to be prescribed and which different classes, including human critically important antibiotics (CIAs). The survey was completed by 3004 practitioners from 25 European countries. Many older antibiotics (eg, penicillins, tetracyclines) are cited most frequently as the prescribed classes to treat the main food producing species. The frequency of citation of non‐CIAs predominates. CIAs are mostly frequently cited to be prescribed for: urinary diseases in cats (62 per cent), respiratory diseases in cattle (45 per cent), diarrhoea in cattle and pigs (respectively 29 per cent and 34 per cent), locomotion disorders in cattle (31 per cent), postpartum dysgalactia syndrome complex in pigs (31 per cent) and dental disease in dogs (36 per cent). Clear 'preferences' between countries can be observed between antibiotic classes. The use of national formularies and guidance helps to drive responsible use of antibiotics and can significantly reduce the extent of use of CIAs. A more widespread introduction of veterinary practice antibiotic prescribing policies and monitoring obedience to these should ensure more widespread compliance with responsible use guidelines.